2016
DOI: 10.1080/15384101.2016.1222339
|View full text |Cite
|
Sign up to set email alerts
|

The long and the short of TRF2 in neurogenesis

Abstract: Gene expression patterns change dramatically during neuronal development. Proliferating cells, including neural stem cells (NSCs), express telomere repeat-binding factor 2 (TRF2), a nuclear protein that associates with telomeric proteins, DNA, and RNA telomeres. In NSCs TRF2 also binds to the transcription regulator REST to facilitate repression of numerous neuron-specific genes, thereby keeping the NSCs in a selfrenewing state. Upon neuronal differentiation, TRF2 levels decline, REST-regulated neuronal genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Using stainings for TRF2 and telomere FISH, we found that some telomeres are preferentially located within ELCS and their immediate proximity. Further evidence supports the idea that telomere-associated proteins are likely to contribute to the regulation of cellular proliferative capacity (Blasco, 2002, Grammatikakis et al., 2016). Previous studies have also shown that telomeres are associated to lamins and lamin-associated proteins such as Lap2, and are rich in epigenetic modifications, as we confirm here for H3K9me3 (Gonzalo and Eissenberg, 2016).…”
Section: Discussionsupporting
confidence: 73%
“…Using stainings for TRF2 and telomere FISH, we found that some telomeres are preferentially located within ELCS and their immediate proximity. Further evidence supports the idea that telomere-associated proteins are likely to contribute to the regulation of cellular proliferative capacity (Blasco, 2002, Grammatikakis et al., 2016). Previous studies have also shown that telomeres are associated to lamins and lamin-associated proteins such as Lap2, and are rich in epigenetic modifications, as we confirm here for H3K9me3 (Gonzalo and Eissenberg, 2016).…”
Section: Discussionsupporting
confidence: 73%
“…The HNRNPH1 and HNRNPH2 proteins have similar function in regulation of pre‐mRNAs splicing; in particular, they are both involved in neuronal cell differentiation by regulating alternative splicing . A study in rat cortical neurons showed that although HNRNPH2 had a slightly lower effect than HNRNPH1, both paralogs acted similarly in controlling splicing of Trf2 through promoting the longer splice variant which inhibited neurogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between TERRA and TRF2 has been proposed to facilitate heterochromatin formation, while TERRA depletion leads to an increase in TIFs (59). Intriguingly, a splice-variant of TRF2 lacking the linker and DBD (similar to TRF2 ΔC ) co-localizes with neuronal granules, ribonuclear biomolecular condensates that facilitate the transport of mRNAs in axons (60, 61). Based on our work here, one interpretation of this observation is that while the shorter TRF2 splice variant loses its ability to interact with telomeres it retains non-specific binding affinity for RNA, possibly via interactions within its basic N-terminus domain.…”
Section: Introductionmentioning
confidence: 99%